Contributions of Francisca Reyes and José Trinidad Reyes to education in the 19th century in Honduras - De Las Heras Ochoa, Jesús (University Magazine, 2022)
Honduran society recognizes the valuable educational contribution of Father José Trinidad Reyes Sevilla, as founder of the university in 1847; however, his contributions to the community of his time were broader in favor of formal and non-formal education; increasing other family efforts that include her niece María Francisca Reyes del Palacio, who carried out an outstanding educational action in favor of the girls of Tegucigalpa during the second half of the 19th century. This research addresses the educational context of Honduras and Central America in the 19th century, some of the social implications of women in education, the educational contributions and the current legacy of Francisca Reyes del Palacio and Father José Trinidad Reyes Sevilla.